To Pixar and beyond my unlikely journey with Steve Jobs to make entertainment history - Levy, Lawrence (Boston Houghton Mifflin Harcourt, 2016)
After Steve Jobs was unceremoniously dismissed from Apple in the early 1990's, while building his failed competitor NeXT, he made a side bet to develop a little-known, barely profitable video graphics company called Pixar. One day, out of the blue, Jobs called Lawrence Levy, a Harvard-trained attorney, in the hope that Jobs could somehow persuade Levy to join forces with him in his quest to energize Pixar. Somehow, despite Pixar's very modest beginnings, Levy, Jobs, and studio chief Ed Catmull, were able to shape it into the world's most creative motion picture company. This is Levy's account of those early beginnings at Pixar, of his friendship with Jobs, and how they were able to join forces to transform Pixar into one of Hollywood's greatest success stories"
Includes index.
Keywords: Levy, Lawrence (Lawrence B.)